2001
DOI: 10.1128/aem.67.11.5267-5272.2001
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Quantification of Snow Algae with an Airborne Imaging Spectrometer

Abstract: We describe spectral reflectance measurements of snow containing the snow alga Chlamydomonas nivalis and a model to retrieve snow algal concentrations from airborne imaging spectrometer data. Because cells of C. nivalis absorb at specific wavelengths in regions indicative of carotenoids (astaxanthin esters, lutein, ␤-carotene) and chlorophylls a and b, the spectral signature of snow containing C. nivalis is distinct from that of snow without algae. The spectral reflectance of snow containing C. nivalis is sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
159
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(169 citation statements)
references
References 17 publications
10
159
0
Order By: Relevance
“…If we knew the total quantity of algae in a given area of snow, we could multiply it by such an integrated rate to obtain daily CO 2 flux. Painter et al (26) in the Sierra Nevada Mountains of California have recently developed the use of remote sensing to estimate snow-algae densities: a trial scan of their field site found a mean concentration of 1,300 cells ml Ϫ1 over an area of 0.495 km 2 of snow. Recent reanalysis of their data suggests that the number should be closer to 300 cells ml Ϫ1 (T. H. Painter, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…If we knew the total quantity of algae in a given area of snow, we could multiply it by such an integrated rate to obtain daily CO 2 flux. Painter et al (26) in the Sierra Nevada Mountains of California have recently developed the use of remote sensing to estimate snow-algae densities: a trial scan of their field site found a mean concentration of 1,300 cells ml Ϫ1 over an area of 0.495 km 2 of snow. Recent reanalysis of their data suggests that the number should be closer to 300 cells ml Ϫ1 (T. H. Painter, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results presented here, together with previous correlative observations [8][9][10][11][12][13][14][15][16] , laboratory experiments 17 , and theoretical calculations 18 , provide a compelling case for the magnitude of the glacier microbiome's effect on hydrology and climate. Snow algae amplify their albedo reduction through life history, population growth, dispersal, and physiology.…”
Section: Implications For High-latitude Ice Sheetsmentioning
confidence: 99%
“…Fresh snow reflects >90% of visible radiation, but during melt its grain size and water content increase, reducing albedo and further increasing snowmelt 1 . Impurities, including black carbon 3 , dust 4 , and resident microbes [7][8][9][10][11][12][13][14][15][16][17][18][19] , also lower albedo; however, microbes differ from non-living particulates in several critical ways. Perennial populations of photosynthetic microbes actively resurface following overwinter burial by snow 20 , and depend on liquid water and nutrients for survival and reproduction 13,14,[20][21][22] .…”
mentioning
confidence: 99%
“…Partitioned estimates of GrIS mass loss have shown that surface melt contributes substantially to annual ice loss (Box, 2013;. Snow and ice surfaces become darker and have reduced visible-to-near-infrared (VNIR) reflectance and albedo due to the deposition of particulates, re-emergence of engrained particulates, biological activity, snow grain metamorphosis and the presence of melt (LaChapelle, 1969;Warren and Wiscombe, 1980;Kohshima et al, 1993;Painter et al, 2001;Takeuchi, 2009;Hodson et al, 2017). As surface melt is both a factor and result of surface darkening, the potential exists for a variety of melt-albedo feedbacks to further enhance shortwave absorption and accelerate melt, increasing mass loss and sea level rise contributions Tedesco et al, 2015).…”
Section: Introductionmentioning
confidence: 99%